Penerapan Model Pembelajaran Kooperatif Tipe Stad dengan Berbantuan Media Balok Hitung, Meningkatkan Hasil Belajar - Erine Roosi Yuliana (Jurnal Syntax Transformation, 2023)
The formulation of the research problem is how the learning process, increasing learning outcomes knowledge and place value skills, and changes in student behavior by applying the STAD (Student Teams Achievement Division) cooperative learning model with the help of counting blocks as media. This research was conducted in two cycles, each cycle three meetings. The subjects of this study were class I students at SD Negeri Podosugih 01 Pekalongan City even semester of the 2021/2022 academic year. There was an increase in the average score from 82 in cycle I to 93 in cycle II, accompanied by a change in behavior for the better